Composition for forming coating film
By using coating compositions of silicone polymers and organic solvents with specific structural units, the insufficient performance of existing coating materials in the formation of low refractive index films is solved, and the coating effect of high hardness, low refractive index and alkali-soluble is achieved.
Patent Information
- Application Number
- JP2023121730
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-26
- Publication Date
- 2025-02-06
AI Technical Summary
When forming a low refractive index film, it is difficult for the existing coating materials to have excellent film formation performance, alkali solubility and reactivity of polymerization initiator reacting with active energy rays, and there is a need for further improvement in the prior art.
Using a coating composition containing a silicone polymer and an organic solvent of a specific structural unit, the silicone polymer is represented by the general formula (1) to (4), the mass ratio of each structural unit is 1:2:3:4, and the sum is 100, and a coating is formed by using a leveling agent and a polymerization initiator.
The coating is achieved with excellent film formation performance, low refractive index and alkali solubility, and can react with active energy rays to form a coating with high hardness.
Smart Images

Figure 2025018216000001 
Figure 2025018216000002 
Figure 2025018216000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a film-forming composition. [Background technology]
[0002] Various lens materials, planarizing films, and other coating materials are used in solid-state imaging devices such as charge coupled devices (CCDs) and complementary metal-oxide semiconductor (CMOS) image sensors, as well as in display substrates and various anti-reflection films.
[0003] Such coating materials are required to have many properties such as heat resistance, low-temperature processability, etc., in addition to optical properties such as transparency and appropriate refractive index. In addition, depending on the application, alkali solubility is also required. It is known that a resin composition containing a siloxane compound is suitable for such requirements.
[0004] For example, Patent Document 1 discloses a composition for forming a low refractive index film, which contains a silicone resin obtained by hydrolysis and condensation of a mixed raw material containing two or more specific silane compounds. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2012-203059 A Summary of the Invention [Problem to be solved by the invention]
[0006] In recent years, there has been a demand for the above-mentioned coating materials to be compositions for forming a coating film that have excellent film-forming properties, a low refractive index, and alkali solubility, and that react with a polymerization initiator by active energy rays. Therefore, there is room for further improvement in the technology disclosed in Patent Document 1.
[0007] Therefore, an object of the present invention is to provide a composition for forming a film, which has excellent film-forming properties, produces a film having a low refractive index and alkali solubility, and reacts with a polymerization initiator by the action of active energy rays. [Means for solving the problem]
[0008] The present inventors have found that the above problems can be solved by using the following coating-forming composition, and have thus completed the present invention.
[0009] That is, the present invention provides a coating-forming composition comprising a siloxane polymer having structural units derived from the following general formulas (1) to (4), and an organic solvent, wherein in the siloxane polymer, when the mass ratio of the structural units derived from the following general formula (1) is w1, the mass ratio of the structural units derived from the following general formula (2) is w2, the mass ratio of the structural units derived from the following general formula (3) is w3, and the mass ratio of the structural units derived from the following general formula (4) is w4, w1 is more than 35 and 60 or less, w2 is 5 to 20, the sum of w3 and w4 is 20 to 60, and w1+w2+w3+w4=100.
[0010] [ka] (In the above general formula (1), R 1 represents an alkyl group. 1 may be the same or different.)
[0011] [ka] (In the above general formula (2), X 1 is a fluoroalkyl group having 3 to 13 fluorine atoms; X 2 is an alkyl group, a siloxy group or a monovalent organic group having a radical polymerizable double bond; R 2 represents an alkyl group. 2 may be the same or different. a is 0 or 1.
[0012] [ka] (In the above general formula (3), Y 1 is an alkyl group, Y 2 is an alkyl group or a siloxy group, R 3 represents an alkyl group. 3 may be the same or different. b is 0 or 1.
[0013] [ka] (In the above general formula (4), Z 1 is a monovalent organic group having a radically polymerizable double bond, Z 2 is an alkyl group or a siloxy group, R 4 represents an alkyl group. 4 may be the same or different. c is 0 or 1.
[0014] In the coating film forming composition of the present invention, the siloxane polymer preferably has w1 of more than 35 and not more than 55, w2 of 5-20, w3 of 15-40, and w4 of 5-25. In the coating composition of the present invention, the siloxane polymer further contains a structural unit derived from the following general formula (5), and the structural unit derived from the following general formula (5) is preferably 1 to 10 parts by mass per 100 parts by mass of the total mass of w1, w2, w3, and w4.
[0015] [ka] (In the above general formula (5), V 1 is an alkyl group substituted with an acid anhydride group, V 2 is an alkyl group or a siloxy group, R 5 represents an alkyl group. 5 may be the same or different. d is 0 or 1.
[0016] In the coating forming composition of the present invention, it is preferable that in the above general formula (2), a is 0, in the above general formula (3), b is 0, and in the above general formula (4), c is 0. In the coating composition of the present invention, d is preferably 0 in the above general formula (5). The coating composition of the present invention preferably contains a leveling agent. The coating composition of the present invention preferably further contains a polymerization initiator. The coating composition of the present invention preferably produces a cured coating having a refractive index of 1.40 to 1.43. The coating composition of the present invention preferably produces a cured coating having a hardness of 5H or more. Effect of the Invention
[0017] The coating composition of the present invention has excellent film-forming properties, and the coating has a low refractive index and alkali solubility, and reacts with a polymerization initiator by the action of active energy rays. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0018] The coating composition of the present invention contains a siloxane polymer having structural units derived from general formulas (1) to (4) described later, and an organic solvent, wherein in the siloxane polymer, when the mass ratio of the structural units derived from general formula (1) described later is w1, the mass ratio of the structural units derived from general formula (2) described later is w2, the mass ratio of the structural units derived from general formula (3) described later is w3, and the mass ratio of the structural units derived from general formula (4) described later is w4, w1 is more than 35 and 60 or less, w2 is 5 to 20, the sum of w3 and w4 is 20 to 60, and w1+w2+w3+w4=100. First, the siloxane polymer will be described.
[0019] (Siloxane polymer) In the coating film forming composition of the present invention, the siloxane polymer has constitutional units derived from the general formulas (1) to (4) described below.
[0020] First, the following general formula (1) will be explained.
[0021] [ka] (In the above general formula (1), R 1 represents an alkyl group. 1 may be the same or different.)
[0022] In the above general formula (1), R 1 is preferably an alkyl group having 1 to 10 carbon atoms. Such an alkyl group is a methyl group, an ethyl group, a propyl group, an isopropyl group, a t-butyl group, a n-butyl group or a sec-butyl group.
[0023] Examples of the above general formula (1) include tetramethoxysilane, tetraethoxysilane, tetra-n-propoxysilane, tetraisopropoxysilane, tetra-n-butoxysilane, and tetraisobutoxysilane. Of these, tetramethoxysilane and tetraethoxysilane are preferred.
[0024] The following general formula (2) will be explained.
[0025] [ka] (In the above general formula (2), X 1 is a fluoroalkyl group having 3 to 13 fluorine atoms; X 2 is an alkyl group, a siloxy group or a monovalent organic group having a radical polymerizable double bond; R 2 represents an alkyl group. 2 may be the same or different. a is 0 or 1.
[0026] In the above general formula (2), X 1 can be appropriately selected depending on the application of the coating of the coating-forming composition. For example, in order to reduce the refractive index, it is preferable to select the number of fluorine atoms in the range of 9 to 13. Furthermore, for example, in order to reduce the refractive index while maintaining hardness, it is preferable to select the number of fluorine atoms in the range of 3 to 5.
[0027] In the above general formula (2), X 2 is preferably an alkyl group having 1 to 10 carbon atoms. Such an alkyl group is a methyl group, an ethyl group, a propyl group, an isopropyl group, a t-butyl group, a n-butyl group or a sec-butyl group.
[0028] In the above general formula (2), R 2 is preferably an alkyl group having 1 to 10 carbon atoms. Such an alkyl group is a methyl group, an ethyl group, a propyl group, an isopropyl group, a t-butyl group, a n-butyl group or a sec-butyl group.
[0029] In the above general formula (2), a is preferably 0.
[0030] Examples of the above general formula (2) include trifluoropropylmethyldimethoxysilane, trifluoropropylmethyldiethoxysilane, trifluoropropylmethyldipropoxysilane, trifluoropropylmethyldiisopropoxysilane, trifluoropropylethyldimethoxysilane, trifluoropropylethyldiethoxysilane, heptadecafluorodecylmethyldimethoxysilane, tridecafluorooctylmethyldimethoxysilane, tridecafluorooctylmethyldiethoxysilane, tridecafluorooctylmethyldipropoxysilane, tridecafluorooctylmethyldiisopropoxysilane, trifluoropropylvinyldimethoxysilane, trifluoropropylvinyldiethoxysilane, and trifluoropropyltrialkoxysilane.
[0031] The following general formula (3) will be explained.
[0032] [ka] (In the above general formula (3), Y 1 is an alkyl group, Y 2 is an alkyl group or a siloxy group, R 3 represents an alkyl group. 3 may be the same or different. b is 0 or 1.
[0033] In the above general formula (3), Y 1 is preferably an alkyl group having 1 to 10 carbon atoms. Such an alkyl group is a methyl group, an ethyl group, a propyl group, an isopropyl group, a t-butyl group, a n-butyl group or a sec-butyl group.
[0034] In the above general formula (3), Y 2 is preferably an alkyl group having 1 to 10 carbon atoms. Such an alkyl group is a methyl group, an ethyl group, a propyl group, an isopropyl group, a t-butyl group, a n-butyl group or a sec-butyl group.
[0035] In the above general formula (3), R 3 is preferably an alkyl group having 1 to 10 carbon atoms. Such an alkyl group is a methyl group, an ethyl group, a propyl group, an isopropyl group, a t-butyl group, a n-butyl group or a sec-butyl group.
[0036] In the above general formula (3), b is preferably 0.
[0037] Examples of the above general formula (3) include methyltrimethoxysilane, methyltriethoxysilane, methyltripoxysilane, methyltriisopropoxysilane, methyltri-n-butoxysilane, methyltri-t-butoxysilane, methyltri-sec-butoxysilane, ethyltrimethoxysilane, ethyltriethoxysilane, propyltrimethoxysilane, butyltrimethoxysilane, pentyltrimethoxysilane, hexyltrimethoxysilane, dimethyldimethoxysilane, and dimethyldiethoxysilane.
[0038] The following general formula (4) will be explained.
[0039] [ka] (In the above general formula (4), Z 1 is a monovalent organic group having a radically polymerizable double bond, Z 2 is an alkyl group or a siloxy group, R 4 represents an alkyl group. 4 may be the same or different. c is 0 or 1.
[0040] In the above general formula (4), Z 1 is preferably a monovalent organic group having a vinyl group, an allyl group, or a (meth)acryloyl group.
[0041] In the above general formula (4), Z 2 is preferably an alkyl group having 1 to 10 carbon atoms. Such an alkyl group is a methyl group, an ethyl group, a propyl group, an isopropyl group, a t-butyl group, a n-butyl group or a sec-butyl group.
[0042] In the above general formula (4), R 4 is preferably an alkyl group having 1 to 10 carbon atoms. Such an alkyl group is a methyl group, an ethyl group, a propyl group, an isopropyl group, a t-butyl group, a n-butyl group or a sec-butyl group.
[0043] In the above general formula (4), c is preferably 0.
[0044] Examples of the general formula (4) include vinyl silane compounds such as vinyl trimethoxy silane, vinyl triethoxy silane, methyl vinyl dimethoxy silane, and methyl vinyl diethoxy silane; 3-(meth)acryloyloxy propyl methyl dimethoxy silane, 3-(meth)acryloyloxy propyl trimethoxy silane, 3-(meth)acryloyloxy propyl ethyl diethoxy silane, and 3-(meth)acryloyloxy propyl triethoxy silane; and allyl silane compounds such as allyl trimethoxy silane and allyl triethoxy silane.
[0045] The siloxane polymer further contains a structural unit derived from the following general formula (5), and the structural unit derived from the following general formula (5) is preferably 1 to 10 parts by mass per 100 parts by mass of the total mass of w1, w2, w3, and w4.
[0046] [ka] (In the above general formula (5), V 1 is an alkyl group substituted with an acid anhydride group, V 2 is an alkyl group or a siloxy group, R 5 represents an alkyl group. 5 may be the same or different. d is 0 or 1.
[0047] In the above general formula (5), V 1 Examples of the alkyl group include succinic anhydride-substituted alkyl groups. Specific examples include a 2-succinic anhydride group-substituted ethyl group, a 3-succinic anhydride group-substituted propyl group, and a 4-succinic anhydride group-substituted butyl group.
[0048] In the above general formula (5), V 2 is preferably an alkyl group having 1 to 10 carbon atoms. Such an alkyl group is a methyl group, an ethyl group, a propyl group, an isopropyl group, a t-butyl group, a n-butyl group or a sec-butyl group.
[0049] In the above general formula (5), R 5 is preferably an alkyl group having 1 to 10 carbon atoms. Such an alkyl group is a methyl group, an ethyl group, a propyl group, an isopropyl group, a t-butyl group, a n-butyl group or a sec-butyl group.
[0050] In the above general formula (5), d is preferably 0.
[0051] Examples of the above general formula (5) include triethoxysilylpropyl succinic anhydride, triethoxysilylbutyl succinic anhydride, and triethoxysilylethyl succinic anhydride.
[0052] In the above siloxane polymer, when the mass ratio of the structural units derived from the above general formula (1) is w1, the mass ratio of the structural units derived from the above general formula (2) is w2, the mass ratio of the structural units derived from the above general formula (3) is w3, and the mass ratio of the structural units derived from the above general formula (4) is w4, w1 is more than 35 and not more than 60, w2 is 5 to 20, the sum of w3 and w4 is 20 to 60, and w1+w2+w3+w4=100. In the above siloxane polymer, it is preferable that w1 is more than 35 and not more than 55, w2 is 5-20, w3 is 15-40, and w4 is 5-25. Furthermore, w1 is preferably 40-50, w2 is preferably 10-20, w3 is preferably 25-35, and w4 is preferably 10-15. The mass ratio of the structural units derived from the above general formulas (1) to (4) is 29 Si-NMR and 1 It can be obtained by measuring by H-NMR.
[0053] When the siloxane polymer has a structural unit derived from the general formula (5), the structural unit derived from the general formula (5) is preferably 1 to 10 parts by mass per 100 parts by mass of the total mass of w1, w2, w3, and w4. By containing the constitutional units derived from the above general formula (5) in such a range, the alkali solubility can be suitably improved.
[0054] The siloxane polymer preferably has a weight average molecular weight (Mw) of 800 to 10,000. If the weight average molecular weight (Mw) is less than 800, the film-forming property and curing property of the composition for forming a coating film may decrease, whereas if the weight average molecular weight (Mw) is more than 10,000, the solubility of the composition for forming a coating film may decrease. The siloxane polymer more preferably has a weight average molecular weight (Mw) of 1,000 to 5,000.
[0055] The weight average molecular weight (Mw) can be measured by dissolving the siloxane polymer to prepare a 0.02 part by mass solution, passing the solution through a filter (GL Sciences, GL Chromatodisk, aqueous 25A, pore size 0.2 μm), and then using Alliance (Nihon Waters) consisting of a size exclusion chromatograph and a refractive index detector under the following conditions. Column: pLgel mixed D (Agilent) x 2 connected in series Detector: alliance (manufactured by Japan Waters) Eluent:THF Flow rate: 1.0 ml / min Injection volume: 100μl
[0056] A method for producing the above siloxane polymer will now be described.
[0057] Examples of the method for producing the siloxane polymer include a method in which the above general formulas (1) to (4) and, if necessary, the above general formula (5) are mixed in an appropriate container, and then water, a polymerization catalyst, and, if necessary, a reaction solvent are added to cause hydrolysis and condensation. After the condensation reaction, unnecessary by-products other than the siloxane polymer are removed by a method such as extraction, dehydration, or solvent removal, thereby obtaining the siloxane polymer.
[0058] The amount of water used in the above reaction is preferably an amount such that the number of water molecules is the same as the number of hydrolyzable substituents of the above general formulas (1) to (4), and if necessary, the above general formula (5), placed in a vessel. In addition, since each molecule of the above general formulas (1) to (5) has 2 to 4 hydrolyzable substituents, the amount of water may be simply set to an amount that is about 3 to 4 times the number of water molecules relative to the total number of molecules of the above general formulas (1) to (5) placed in the container.
[0059] As the polymerization catalyst, for example, an acid catalyst such as acetic acid or hydrochloric acid, or a base catalyst such as ammonia, triethylamine, cyclohexylamine or tetramethylammonium hydroxide can be used.
[0060] The amount of the polymerization catalyst is preferably such that the number of molecules of the polymerization catalyst is about 0.05 to 0.2 times the number of all molecules of the general formulas (1) to (5).
[0061] As the reaction solvent, preferred are lower alcohols such as ethanol, n-propyl alcohol, isopropyl alcohol, etc.; ketone compounds such as acetone, methyl ethyl ketone, etc.; and ester compounds such as ethyl acetate, n-propyl acetate, etc. Among these, lower alcohols are more preferred, and ethanol and isopropyl alcohol are even more preferred from the viewpoints of being able to maintain a moderate reaction temperature and being easy to distill off.
[0062] The reaction temperature is preferably 60 to 80° C., and the reaction time is preferably about 2 to 24 hours so that the reaction proceeds sufficiently.
[0063] (Organic solvent) Next, the organic solvent will be described.
[0064] As the organic solvent, organic solvents such as alcohols, polyhydric alcohols and their derivatives, ketone-based organic solvents, and ester-based organic solvents can be used.
[0065] Examples of the alcohols include lower alcohols such as methanol, ethanol, n-propyl alcohol-n-, isopropyl alcohol, n-butyl alcohol, isobutyl alcohol, and sec-butyl alcohol.
[0066] Examples of the polyhydric alcohols include ethylene glycol, propylene glycol, 1,2-butanediol, 1,3-butanediol, diethylene glycol, and dipropylene glycol.
[0067] Examples of derivatives of the polyhydric alcohols include glycol monoethers such as ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol mono-n-propyl ether, ethylene glycol monoisopropyl ether, ethylene glycol mono-n-butyl ether, ethylene glycol monoisobutyl ether, ethylene glycol monophenyl ether, propylene glycol monomethyl ether, propylene glycol monoethyl ether, propylene glycol mono-n-propyl ether, propylene glycol monoisopropyl ether, propylene glycol mono-n-butyl ether, propylene glycol monoisobutyl ether, propylene glycol monophenyl ether, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, diethylene glycol mono-n-propyl ether, diethylene glycol monoisopropyl ether, diethylene glycol mono-n-butyl ether, diethylene glycol monoisobutyl ether, dipropylene glycol monomethyl ether, dipropylene glycol monoethyl ether, dipropylene glycol-n-propyl ether, dipropylene glycol isopropyl ether, dipropylene glycol-n-butyl ether, and dipropylene glycol isobutyl ether. Further, for example, ethylene glycol monomethyl ether acetate, ethylene glycol monomethyl ether propionate, ethylene glycol monoethyl ether acetate, ethylene glycol mono-n-propyl ether acetate, ethylene glycol monoisopropyl ether acetate, ethylene glycol mono-n-butyl ether acetate, ethylene glycol monoisobutyl ether acetate, propylene glycol monomethyl ether acetate, propylene glycol monoethyl ether acetate, propylene glycol mono-n-propyl ether acetate, propylene glycol monoisopropyl ether acetate, propylene glycol mono-n-butyl ether acetate, propylene glycol monoisobutyl ether acetate, diethyl ether acetate, ethylene glycol monomethyl ether acetate, ethylene glycol monoethyl ether acetate, propylene glycol mono-n-propyl ether acetate, propylene glycol monoisopropyl ether acetate, propylene glycol mono-n-butyl ether acetate, propylene glycol monoisobutyl ether acetate, Examples of the glycol monoether acylates include ethylene glycol monomethyl ether acetate, diethylene glycol monoethyl ether acetate, diethylene glycol mono-n-propyl ether acetate, diethylene glycol monoisopropyl ether acetate, diethylene glycol mono-n-butyl ether acetate, diethylene glycol monoisobutyl ether acetate, dipropylene glycol monomethyl ether acetate, dipropylene glycol monoethyl ether acetate, dipropylene glycol mono-n-propyl ether acetate, dipropylene glycol monoisopropyl ether acetate, dipropylene glycol mono-n-butyl ether acetate, and dipropylene glycol monoisobutyl ether acetate.
[0068] Examples of the ketone organic solvent include acetone, methyl ethyl ketone, methyl-n-propyl ketone, methyl isopropyl ketone, methyl-n-butyl ketone, methyl isobutyl ketone, and cyclohexanone.
[0069] Examples of the ester-based organic solvent include ethyl acetate, n-propyl acetate, isopropyl acetate, n-butyl acetate, isobutyl acetate, n-amyl acetate, isoamyl acetate, methyl propionate, ethyl propionate, methyl lactate, ethyl lactate, and n-propyl lactate.
[0070] The organic solvents may be used alone or in combination of two or more kinds.
[0071] From the viewpoints of solubility of the above-mentioned siloxane polymer and coating suitability, derivatives of secondary alcohols and ester-based organic solvents are preferred, and propylene glycol monomethyl ether, propylene glycol monoethyl ether, propylene glycol mono-n-propyl ether, propylene glycol monoisopropyl ether, propylene glycol mono-n-butyl ether, propylene glycol monoisobutyl ether, propylene glycol monomethyl ether acetate, n-propyl acetate, and isopropyl acetate are more preferred.
[0072] (Leveling agent) The coating composition of the present invention may contain a leveling agent.
[0073] Examples of the leveling agent include silicone surfactants and fluorine surfactants. Among these, silicone-based surfactants are more suitable as the leveling agent in the present invention.
[0074] The content of the leveling agent is preferably 0.05 to 1 part by mass with respect to 100 parts by mass of the siloxane polymer.
[0075] (Photopolymerizable compound) The coating composition of the present invention preferably contains a polymerization initiator and, if necessary, a photopolymerizable compound depending on the required performance. First, the photopolymerizable compound will be described.
[0076] The photopolymerizable compound is preferably a photopolymerizable compound having two or more radically polymerizable unsaturated double bonds.
[0077] Examples of the photopolymerizable compound having two or more radically polymerizable unsaturated double bonds include ester compounds of divalent or higher hydroxyl group-containing compounds and (meth)acrylic acid, such as 1,3-butylene glycol di(meth)acrylate, 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, neopentyl glycol di(meth)acrylate, tricyclodecane dimethanol di(meth)acrylate, diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, dipropylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, tetrapropylene ... Examples of the acrylates include propylene glycol di(meth)acrylate, tetrapropylene glycol di(meth)acrylate, bisphenol A di(meth)acrylate, tris(2-hydroxyethyl)isocyanuric acid di(meth)acrylate, trimethylolpropane tri(meth)acrylate, glycerin tri(meth)acrylate, pentaerythritol tri(meth)acrylate, tris(2-hydroxyethyl)isocyanuric acid tri(meth)acrylate, ditrimethylolpropane tetra(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, and dipentaerythritol hexa(meth)acrylate.
[0078] Among these, from the viewpoint of being able to increase the crosslink density and impart excellent hardness to the cured coating, compounds having three or more reactive functional groups, for example, trimethylolpropane tri(meth)acrylate, glycerin tri(meth)acrylate, pentaerythritol tri(meth)acrylate, tris(2-hydroxyethyl)isocyanuric acid tri(meth)acrylate, ditrimethylolpropane tetra(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, and dipentaerythritol hexa(meth)acrylate are preferred, with tris(2-hydroxyethyl)isocyanuric acid tri(meth)acrylate and dipentaerythritol hexa(meth)acrylate being more preferred.
[0079] The photopolymerizable compound is preferably contained in an amount of 10 to 50 parts by mass relative to 100 parts by mass of the siloxane polymer. If the content of the photopolymerizable compound is less than 10 parts by mass per 100 parts by mass of the siloxane polymer, the curing properties of the cured coating film and its adhesion to the light-transmitting substrate or ITO electrode may be insufficient. If the content of the photopolymerizable compound is more than 50 parts by mass per 100 parts by mass of the siloxane polymer, the solubility of the uncured coating film in the developer may be insufficient.
[0080] (Polymerization initiator) As the polymerization initiator, it is preferable to use a polymerization initiator that can provide a sufficient photocuring reaction when forming a cured coating by the photolithography method described below.
[0081] Examples of the polymerization initiator include benzil, benzoin, benzophenone, camphorquinone, 2,2-dimethoxy-1,2-diphenylethane-1-one, 4,4'-bis(dimethylamino)benzophenone, 4,4'-bis(diethylamino)benzophenone, 2-hydroxy-2-methyl-1-phenylpropan-1-one, 1-hydroxycyclohexyl phenyl ketone, 2,2-dimethoxy-2-phenylacetophenone, 2-methyl-[4'-(methylthio)phenyl]-2-morpholino-1-propanone, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-butan-1-one, 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide, and the like. Examples of such compounds include carbonyl compounds such as sphingoside oxides; trihalomethanes such as 1,3-bis(trichloromethyl)-5-(2'-chlorophenyl)-1,3,5-triazine and 2-[2-(2-furanyl)ethylenyl]-4,6-bis(trichloromethyl)-1,3,5-triazine; imidazole dimers such as 2,2'-bis(2-chlorophenyl)-4,5,4',5'-tetraphenyl-1,2'-biimidazole; thioxanthone compounds such as 2-isopropylthioxanthone, 2,4-dimethylthioxanthone, 2,4-diethylthioxanthone, and 2,4-dichlorothioxanthone; and biguanide compounds such as 1,2-diisopropyl-3-[bis(dimethylamino)methylene]guanidinium=2-(3-benzoylphenyl)propionate.
[0082] These polymerization initiators can be used alone or in combination of two or more kinds, and can also be combined with any photosensitizer. Furthermore, a photoacid generator or a photobase generator can be used in combination as a catalyst for accelerating the condensation reaction of the siloxane polymer.
[0083] The polymerization initiator is preferably contained in an amount of 0.5 to 40 parts by mass when the total amount of the siloxane polymer and the photopolymerizable compound is taken as 100 parts by mass.
[0084] If the content of the polymerization initiator is less than 0.5 parts by mass, the photopolymerizability may decrease, and unreacted components may remain in the exposed area in the photolithography method. If the content of the polymerization initiator is more than 40 parts by mass, the storage stability of the coating composition may decrease. The amount of the polymerization initiator is more preferably 1 to 20 parts by mass when the total amount of the siloxane polymer and the polymerizable monomer having two or more radically polymerizable unsaturated double bonds is 100 parts by mass.
[0085] (Other materials) To the coating composition of the present invention, there can be added, within the scope of not decreasing the effects of the present invention, chelate compounds of metals such as aluminum, zirconium, titanium, etc.; carbodiimide-based, isocyanate-based, and crosslinking agents having crosslinkable functional groups such as epoxy groups and thiol groups; silicone-based, fluorine-based, and other surfactants; photosensitizers such as aromatic hydrocarbon-based, amino compound-based, nitro compound-based, quinones, and xanthones; polymerization inhibitors such as hydroquinone, methoquinone, hindered amine-based, hindered phenol-based, di-t-butylhydroquinone, 4-methoxyphenol, butylhydroxytoluene, and nitrosamine salts; and fillers such as inorganic metal oxides and organic fine particles.
[0086] (Method of producing a film-forming composition) As a method for producing the coating composition of the present invention, a method can be used in which an organic solvent is charged into an appropriate container, and while stirring with, for example, a high-speed stirrer, the siloxane polymer, if necessary the photopolymerizable compound having two or more radically polymerizable unsaturated double bonds, the polymerization initiator, and other materials are charged and mixed. The method for producing the coating composition of the present invention is not limited to the above-mentioned method, and the order in which the materials are charged may be arbitrary. Furthermore, if a solid material is soluble in an organic solvent, it may be dissolved in advance before being charged, or if it is dispersible in an organic solvent directly or with the aid of a dispersant or the like, it may be dispersed in advance before being charged.
[0087] (Method for forming hardened film) A method for forming a cured coating using the coating composition of the present invention preferably includes a coating step of coating the coating composition onto a substrate, an exposure step of irradiating an exposed area with active energy rays to form a cured coating, and a development step of dissolving and removing the coating liquid in the unexposed area with a developer. After the coating step, the composition may be thermally cured.
[0088] The coating method in the coating step, the active energy rays irradiated to the exposed area in the exposure step and the irradiation method thereof, and the developer for removing the coating liquid from the exposed area can be appropriately selected from those and methods used in conventional photolithography methods.
[0089] For example, the composition for forming a coating film is diluted so that the concentration of the non-volatile components becomes 20% by mass, and then coated using a spin coater, heated (pre-baked) at 80°C for 3 minutes, and then heated at 100 mJ / cm using a mask aligner. 2 A test pattern is baked under the above irradiation conditions, immersed in a developer for 1 minute, and then heated (post-baked) at 150°C for 30 minutes, etc. to obtain a hardened coating. The pre-baking conditions are preferably 60 to 130° C. and 1 to 3 minutes. The above irradiation conditions are 50 to 260 mJ / cm 2 It is preferable that: The post-baking is preferably performed under conditions of 120 to 250° C. for 30 to 60 minutes.
[0090] The heat curing may be carried out, for example, by heating at 130° C. for 10 minutes and then at 230° C. for 30 minutes.
[0091] (Physical properties of coating) The coating film of the coating composition of the present invention has a low refractive index and alkali solubility, and reacts with a photopolymerizable compound by the action of active energy rays.
[0092] The coating composition of the present invention preferably produces a cured coating having a refractive index of 1.40 to 1.43.
[0093] The refractive index was measured by diluting the coating composition with propylene glycol monomethyl ether so that the concentration of non-volatile components was 20% by mass, and applying each coating composition to a commercially available 50 mm square soda glass substrate at 500 rpm for 60 seconds using a spin coater (MS-A100, manufactured by Mikasa Corporation), followed by heat treatment at 130°C and 230°C for 30 minutes to prepare a sample for evaluating the refractive index. A reflection spectroscopic film thickness meter ("FE3000", manufactured by Otsuka Electronics Co., Ltd.) was used to measure the reflectance of the refractive index evaluation sample in the range of 400 to 800 nm. The nkCauchy dispersion equation was quoted as an approximation equation for the wavelength dispersion of the refractive index, and the unknown parameters were found from the actual measured values of the absolute reflectance spectrum using the nonlinear least squares method to calculate the refractive index at a wavelength of 550 nm.
[0094] If the refractive index after the heat treatment at 130° C. and 180° C. is 1.43 or less, it can be determined that the film has a sufficiently low refractive index.
[0095] The refractive index is preferably 1.42 or less, and more preferably 1.41 or less.
[0096] The alkali solubility of the thermosetting coating of the coating composition of the present invention is evaluated based on the solubility rate. The solubility rate (in an aqueous solution of tetramethylammonium hydroxide (mass concentration: 2.38%)) measured by the following method is preferably 50 nm / sec or more, more preferably 100 nm / sec or more. If the dissolution rate is 50 nm / sec or more, it can be determined that the material has alkali solubility.
[0097] The dissolution rate can be measured by the following method. The coating composition was diluted with propylene glycol monomethyl ether so that the concentration of non-volatile components was 20% by mass, and each coating composition was applied to a commercially available 50 mm square soda glass substrate using a spin coater (MS-A100, manufactured by Mikasa Co., Ltd.) at 500 rpm for 60 seconds, and then heat-treated at 130°C for 180 seconds. The film is then immersed in an aqueous solution of tetramethylammonium hydroxide (mass concentration: 2.38%) for 60 seconds. The film thickness of the immersed portion is measured before and after immersion, and the film thickness reduction (nm) / time is evaluated as the dissolution rate. However, to determine the film thickness, three scratches were made with a cutter within a 3 mm range on the coated plate, and the plate was scanned using a surface roughness measuring device (KLA-Tencor Corporation Surface Profiler ALPHA-STEP IQ) to measure the depth, and the average value of the three points was calculated to determine the film thickness.
[0098] The film-forming composition of the present invention reacts with a polymerization initiator and, if necessary, a photopolymerizable compound by active energy rays, and can be used as a film-forming composition for resists.
[0099] Even when used in a resist film-forming composition, it is preferred that the non-exposed areas have alkali solubility.
[0100] Even when the coating film-forming composition of the present invention is used as a coating film-forming composition for a resist, the alkali solubility of the unexposed area is evaluated based on the solubility rate. When used in the above resist, the alkali solubility of the unexposed area can be measured by the following method. 5% by mass of bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide is added to 95% by mass of the composition for forming a resist film and stirred to prepare a composition for forming a resist film. Each of the resist film-forming compositions is applied to a commercially available soda glass substrate of 50 mm square at 500 rpm for 60 seconds using a spin coater (MS-A100, manufactured by Mikasa Corporation). Next, after heating (pre-baking) at 130°C for 30 seconds, a mask aligner (PLA-501FA, Canon) was used to apply 200 mJ / cm 2 The test pattern is baked under the irradiation conditions and then heated at 130°C for 1 minute to prepare a test piece for resist evaluation. The resist evaluation test piece is immersed in a 2.38% tetramethylammonium hydroxide (TMAH) aqueous solution. The film thickness of the immersed non-exposed area is measured before and after immersion. The film thickness reduction (nm) / time is evaluated as the dissolution rate. However, to determine the film thickness, three scratches were made with a cutter within a 3 mm range on the coated plate, and the plate was scanned using a surface roughness measuring device (KLA-Tencor Corporation Surface Profiler ALPHA-STEP IQ) to measure the depth, and the average value of the three points was calculated to determine the film thickness.
[0101] When the composition for forming a coating film of the present invention is used as a composition for forming a resist coating film, it is preferred that the exposed area is excellent in erosion evaluation. Incidentally, when the erosion evaluation is judged to be excellent in the following evaluation, it means that the polymerization initiator has sufficiently reacted with the active energy rays.
[0102] The erosion evaluation of the exposed area of the composition for forming a resist film can be measured by the following method. A test piece for resist evaluation is prepared by the method described above. The resist evaluation test piece is exposed to an aqueous solution of tetramethylammonium hydroxide (TMAH) (pH=11.58) to evaluate erosion of the exposed area. (Developer immersed area / Developer not immersed area)×100≧90% If so, it can be judged that the erosion evaluation is excellent.
[0103] When the composition for forming a coating of the present invention is used as a composition for forming a resist coating, it is preferred that the coating have excellent adhesion.
[0104] The adhesion was confirmed by cutting the coating film of the resist evaluation test piece with a cutter, attaching tape to the surface, and peeling it off according to the standard test conditions of ASTM D-3359-08. In the cut / tape test after chemical treatment, peeling is preferably 0% or more and less than 15%, more preferably less than 5%, and even more preferably 0%.
[0105] The present specification discloses the following:
[0106] The present disclosure (1) is a coating-forming composition comprising a siloxane polymer having structural units derived from the above general formulas (1) to (4) and an organic solvent, wherein in the siloxane polymer, when the mass ratio of the structural units derived from the above general formula (1) is w1, the mass ratio of the structural units derived from the above general formula (2) is w2, the mass ratio of the structural units derived from the above general formula (3) is w3, and the mass ratio of the structural units derived from the above general formula (4) is w4, w1 is more than 35 and 60 or less, w2 is 5 to 20, the sum of w3 and w4 is 20 to 60, and w1+w2+w3+w4=100. Disclosure (2) of the present invention is the composition for forming a coating according to Disclosure (1) of the present invention, in which the siloxane polymer has w1 of more than 35 and not more than 55, w2 of 5-20, w3 of 15-40, and w4 of 5-25. The present disclosure (3) is the coating-forming composition according to the present disclosure (1) or (2), wherein the siloxane polymer further contains a structural unit derived from the above general formula (5), and the structural unit derived from the above general formula (5) is 1 to 10 parts by mass per 100 parts by mass of the total mass of w1, w2, w3, and w4. The present disclosure (4) is a coating-forming composition according to the present disclosures (1) to (3), in which a in the above general formula (2) is 0, b in the above general formula (3) is 0, and c in the above general formula (4) is 0. The present disclosure (5) is the composition for forming a coating according to the present disclosure (3), in which d is 0 in the above general formula (5). The present disclosure (6) is a composition for forming a coating according to any one of the present disclosures (1) to (5), which contains a leveling agent. The present disclosure (7) is the composition for forming a coating according to any one of the present disclosures (1) to (6), further comprising a polymerization initiator. The present disclosure (8) is the composition for forming a coating according to any one of the present disclosures (1) to (7), in which the refractive index of the cured coating is 1.40 to 1.43. The present disclosure (9) is the composition for forming a coating according to any one of the present disclosures (1) to (8), which forms a cured coating having a hardness of 5H or more. EXAMPLES
[0107] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples. Unless otherwise specified, "%" means "% by mass" and "parts" means "parts by mass".
[0108] The following materials were used in the synthesis of the siloxane polymer and the preparation of the coating composition. <Silane compound of general formula (1)> Tetraethoxysilane (A-1) <Silane compound of general formula (2)> Trifluoropropyltrimethoxysilane (B-1) Perfluorohexylethyltrimethoxysilane (B-2) <Silane compound of general formula (3)> Methyltriethoxysilane (C-1) <Silane compound of general formula (4)> Vinyltrimethoxysilane (D-1) <Silane compound of general formula (5)> Triethoxysilylpropyl succinic anhydride (E-1) <Leveling agent> BYK-310(F-1)
[0109] (Synthesis of siloxane polymer and preparation of film-forming composition) In a reaction vessel equipped with a stirrer, reflux condenser, thermometer, and dropping funnel, silane compounds (A-1 to E-1) were dissolved in 2-methoxy-1-propanol in the compounding ratios shown in Table 1. 15 g of 0.045% nitric acid aqueous solution was added dropwise thereto, and the mixture was stirred for 300 minutes under reflux. The reaction by-products, methanol, ethanol, and water, were distilled off under reduced pressure to synthesize a siloxane polymer, and then 0.1 g of (F-1) was added to obtain coating-forming compositions of Examples 1 to 4 and Comparative Examples 1 and 2 with a solid content concentration of about 20 parts by mass.
[0110] (Measurement of weight average molecular weight (Mw) of siloxane polymer) The solvent of each of the coating film forming compositions of Examples 1 to 4 and Comparative Examples 1 and 2 was removed by distillation under reduced pressure, and then the composition was dissolved in THF to prepare 0.02 parts by mass of a solution. Next, the solution was passed through a filter (GL Sciences, GL Chromatodisk, aqueous 25A, pore size 0.2 μm) and then measured under the following conditions using Alliance (Nihon Waters), which is composed of a size exclusion chromatograph and a refractive index detector. Column: pLgel mixed D (Agilent) x 2 connected in series Detector: alliance (manufactured by Japan Waters) Eluent:THF Flow rate: 1.0ml / min Injection volume: 100μl
[0111] [Table 1]
[0112] <Evaluation of film-forming properties of thermosetting coating> Each of the coating compositions of Examples 1 to 4 and Comparative Examples 1 and 2 was diluted with propylene glycol monomethyl ether so that the concentration of non-volatile components was 20% by mass, and each coating composition was applied to a commercially available 50 mm square soda glass substrate using a spin coater (MS-A100, manufactured by Mikasa Co., Ltd.) at 500 rpm for 60 seconds, followed by heat treatment at 80° C. for 3 minutes. Evaluation was performed by observing the film surface with a microscope. <Evaluation criteria> ○: No agglomeration ×: Aggregation occurs
[0113] <Evaluation of Alkaline Solubility of Heat-Cured Coating> Each of the compositions for forming a coating film of Examples 1 to 4 and Comparative Examples 1 to 2 was diluted with propylene glycol monomethyl ether so that the concentration of non-volatile components was 20% by mass, and each composition for forming a coating film was applied to a commercially available 50 mm square soda glass substrate at 500 rpm for 60 seconds using a spin coater (MS-A100, manufactured by Mikasa Co., Ltd.), and heat-treated at 130° C. for 180 seconds to prepare a test piece for evaluating alkali solubility. Next, the test piece was immersed in an aqueous solution of tetramethylammonium hydroxide (mass concentration 2.38%), and the film thickness of the immersed portion was measured before and after immersion, and the film thickness reduction (nm) / time was evaluated as the dissolution rate. However, to determine the film thickness, three scratches were made with a cutter within a 3 mm range on the coated plate, and the plate was scanned using a surface roughness measuring device (KLA-Tencor Corporation Surface Profiler ALPHA-STEP IQ) to measure the depth, and the average value of the three points was calculated to determine the film thickness. <Evaluation criteria> ◎: Dissolution rate is 100nm / sec or more 〇: Dissolution rate is 50nm / sec or more and less than 100nm / sec ×: Dissolution rate is less than 50 nm / sec or insoluble
[0114] <Creating test pieces for evaluating the refractive index and pencil hardness of heat-cured coatings> Each of the coating compositions of Examples 1 to 4 and Comparative Examples 1 and 2 was diluted (with propylene glycol monomethyl ether) so that the concentration of non-volatile components was 20%, and each coating composition was applied to a commercially available 50 mm square soda glass substrate using a spin coater (MS-A100, manufactured by Mikasa Corporation) under coating conditions of 500 rpm and 60 seconds. Next, the sample was heated at 130° C. for 10 minutes and then at 230° C. for 30 minutes to prepare a test piece for evaluating the refractive index and pencil hardness.
[0115] <Evaluation of refractive index> The refractive index was evaluated by measuring the reflectance of the above-mentioned evaluation test piece in the range of 400 to 800 nm using a reflection spectroscopic film thickness meter ("FE3000", manufactured by Otsuka Electronics Co., Ltd.), quoting the nkCauchy dispersion formula as an approximation formula for the wavelength dispersion of the refractive index, determining unknown parameters from the actual measured values of the spectrum of the absolute reflectance using the nonlinear least squares method, and calculating the refractive index at a wavelength of 550 nm. A refractive index of 1.43 or less was judged to be acceptable.
[0116] <Pencil hardness> The evaluation test pieces were measured for pencil hardness (Mitsubishi Pencil Co., Ltd., Uni) according to JIS K 5400-5-4. Pencil hardness of 5H or more was judged to be acceptable.
[0117] (Preparation of composition for forming resist film) To 95% by mass of each of the compositions for forming resist films in Examples 1 to 4 and Comparative Examples 1 and 2, 5% by mass of bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide was added as a polymerization initiator and stirred to prepare compositions for forming resist films.
[0118] <Alkaline solubility of resist film (unexposed area)> Each of the resist film-forming compositions of Examples 1 to 4 and Comparative Examples 1 and 2 was applied to a commercially available soda glass substrate having a size of 50 mm square at 500 rpm for 60 seconds using a spin coater (MS-A100, manufactured by Mikasa Corporation). Next, after heating (pre-baking) at 130°C for 30 seconds, a mask aligner (PLA-501FA, Canon) was used to apply 200 mJ / cm 2 A test pattern was baked under the above irradiation conditions, and a heat treatment was then performed at 130° C. for 1 minute to prepare a test piece for resist evaluation. The resist evaluation test piece was immersed in a tetramethylammonium hydroxide (TMAH) aqueous solution with a mass concentration of 2.38%, and the film thickness of the non-exposed area was measured before and after immersion. The film thickness reduction (nm) / hour was evaluated as the dissolution rate. However, to determine the film thickness, three scratches were made with a cutter within a 3 mm range on the coated plate, and the plate was scanned using a surface roughness measuring device (KLA-Tencor Corporation Surface Profiler ALPHA-STEP IQ) to measure the depth, and the average value of the three points was calculated to determine the film thickness. <Dissolution rate evaluation criteria> ◎: Dissolution rate is 100nm / sec or more ○: Dissolution rate is 50nm / sec or more and less than 100nm / sec ×: Dissolution rate is less than 50 nm / sec or insoluble
[0119] (Evaluation criteria for erosion of exposed areas of resist film) The resist evaluation test pieces prepared by the above-mentioned method were exposed to an aqueous solution of tetramethylammonium hydroxide (TMAH) (pH=11.58) to evaluate erosion of the exposed areas. <Evaluation criteria> ◎:(Developer immersed area / Developer not immersed area)×100=100% 〇:100%>(Developer immersed area / Developer not immersed area)×100≧90% ×:90%>(Developer immersed area / Developer not immersed area)×100
[0120] The adhesion was evaluated by cutting the coating film of the resist evaluation test piece with a cutter, applying tape to the surface, and peeling it off according to the standard test conditions of ASTM D-3359-08 to confirm chemical resistance. In the cut / tape test after chemical treatment, the degree to which the coating film peeled off was rated from 0B to 5B based on the standard test method, with 5B being the most excellent performance. <Evaluation criteria> 5B: 0% peeling 4B: Less than 5% peeling 3B: Peeling of 5% to less than 15% 2B: Peeling of 15% or more but less than 35% 1B: Peeling of 35% or more but less than 65% 0B: 65% or more peeling
[0121] [Table 2]
[0122] As shown in Table 2, it was confirmed that the siloxane polymers of the present invention in Examples 1 to 4 have high solubility in an aqueous TMAH solution and form cured coatings with refractive indices of 1.41 to 1.43 and hardnesses of 5H or greater. Furthermore, it was shown that by performing UV irradiation and heat treatment in the presence of a polymerization initiator, a coating composition with high adhesion that enables pattern formation using an aqueous TMAH solution was formed. [Industrial Applicability]
[0123] The coating composition of the present invention is suitably used for optical lenses such as microlens arrays for solid-state imaging devices, planarizing films, insulating films, protective films, anti-reflection films, anti-reflection films, anti-reflection plates, optical filters, and the like for solar cells, liquid crystals, organic EL (electroluminescence), plasma displays, and LED (Light emitting diode) lighting devices.
Claims
1. The composition contains a siloxane polymer having structural units derived from the following general formulas (1) to (4) and an organic solvent, In the siloxane polymer, the mass ratio of the structural unit derived from the following general formula (1) is w 1 The mass ratio of the structural unit derived from the following general formula (2) is w 2 The mass ratio of the structural unit derived from the following general formula (3) is w 3 The mass ratio of the structural unit derived from the following general formula (4) is w 4 When W 1 is more than 35 and less than 60, w 2 5 to 20, w 3 And w 4 The sum of is 20 to 60, and w 1 +w 2 +w 3 +w 4 = 100 Composition for film formation. 【Chemistry 1】 (In the general formula (1), R 1 represents an alkyl group. 1 may be the same or different.) 【Chemistry 2】 (In the general formula (2), X 1 represents a fluoroalkyl group having 3 to 13 fluorine atoms; X 2 is an alkyl group, a siloxy group or a monovalent organic group having a radical polymerizable double bond; R 2 represents an alkyl group. 2 may be the same or different. a is 0 or 1. 【Chemistry 3】 (In the above general formula (3), Y 1 is an alkyl group, Y 2 is an alkyl group or a siloxy group, R 3 represents an alkyl group. 3 may be the same or different; b is 0 or 1. 【Chemistry 4】 (In the general formula (4), Z 1 represents a monovalent organic group having a radically polymerizable double bond; Z 2 is an alkyl group or a siloxy group, R 4 represents an alkyl group. 4 may be the same or different; c is 0 or 1.
2. The siloxane polymer is 1 is more than 35 and less than 55, w 2 5 to 20, w 3 is 15 to 40, and w 4 2. The coating composition according to claim 1, wherein the molecular weight is 5 to 25.
3. The siloxane polymer further contains a structural unit derived from the following general formula (5), and the structural unit derived from the following general formula (5) is 1 , W 2 , W 3 and w 4 3. The composition for forming a coating film according to claim 1, wherein the amount of the composition for forming a coating film is 1 to 10 parts by mass per 100 parts by mass of the total mass of the above. 【Chemistry 5】 (In the general formula (5), V 1 is an alkyl group substituted with an acid anhydride group; V 2 is an alkyl group or a siloxy group, R 5 represents an alkyl group. 5 may be the same or different. d is 0 or 1.
4. 3. The composition for forming a coating film according to claim 1, wherein in said general formula (2), a is 0, in said general formula (3), b is 0, and in said general formula (4), c is 0.
5. The composition for forming a coating film according to claim 3, wherein in the general formula (5), d is 0.
6. The composition for forming a coating film according to claim 1 or 2, further comprising a leveling agent.
7. The composition for forming a coating film according to claim 1 or 2, further comprising a polymerization initiator.
8. 3. The coating composition according to claim 1, wherein the refractive index of the cured coating is from 1.40 to 1.
43.
9. 3. The coating composition according to claim 1, which produces a cured coating having a hardness of 5H or more.
Citation Information
Patent Citations
Composition for forming low-refractive index film, method for manufacturing low-refractive index thin film, and component with Anti-reflection film
JP2012203059A
Cited By
Branched organopolysiloxane, curable composition, and use thereof
WO2026181933A1